Building Inclusive Climate Capacity: Co-developing Kenya’s Climate Risk Management Curriculum Across Agricultural Livelihoods - Grossi, Amanda; Dinku, Tufa; Hansen, James; Ruirie, Onesmus; Dinh, Dannie; Crane, Todd A.; Murage, Paul; Mugo, Grace; Chege, Patrick (2025)
Kenya’s agricultural sector—encompassing crops, livestock, and fisheries—is increasingly threatened by climate variability, underscoring the need for stronger capacities to interpret and apply climate information in extension and advisory services. In response, the Ministry of Agriculture and Livestock Development (MoALD), with support from the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project and national, regional, and international partners, co-developed the Climate Risk Management in Agricultural Extension (CRMAE–Kenya) curriculum between 2023 and 2025. Through a structured, multisectoral co-production process involving national consultative workshops, technical reviews, and validation exercises, the curriculum was expanded to serve all major agricultural subsectors—crops, livestock, fisheries, irrigation, and cooperatives—and harmonized with Kenya’s national climate and agriculture priorities, including the National Framework for Climate Services.